Signs associated with figurative representations Aurignacian. Examples from Grotte Chauvet and the Swabian Jura. (5th February 2019) - Igarashi, Jannu; Floss, Harald
Abstract: Signs in Upper Palaeolithic art provide an important criterion of assessing cultural affinities or differences. The Swabian Jura in southern Germany and Grotte Chauvet in the Ardèche region in southern France – both inscribed in the list of the UNESCO world heritage - supply the most important examples of Aurignacian art known so far. Of a particular interest in this respect are characteristic types of signs which can be associated with depictions of animals. This paper examines the distinctive ways in which this association is realized in these two regions, including the question which type of signs was employed. Despite of the small data base and the lack of sophisticated statistical tests, this study may help to provide first hints to the question if the Aurignacian groups of the Ardèche and the Swabian Jura, whose areas are linked by important river systems, used similar or different sets of signs and in which animal contexts these signs were used. These results may give indications to what extent these groups were part of the same or different cultural entities and subsequently shared feelings of a common ethnicity and belief-world or not.